PENGEMBANGAN METODE PENYEIMBANGAN LANGSUNG TANPA MENGGUNAKAN MASSA COBA - Iskandar, Ishak S; Abidin, Zainal; Bagiasna, Komang (Mesin, 1996)
This paper deals with the development of direct balancing method that uses no trial mass. This activity is the continuation work of the previous research on semi automation of balancing machine that has been performed at the Dynamics Laboratory IUC-ES ITB. This method has been developed by using Frequency Response Function (FRF) data of a balancing machine as a function of frequency and rotors masses that will be balanced. These FRF data are used as aconversion factor of voltage, which is the output of velocity transducer, to unbalance ï¬zrce. Using this method, the balancing process can be perï¬armed faster and more accurately than that of conventional balancing methods.